1999
DOI: 10.1038/sj.leu.2401334
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α protects myeloma cell lines from dexamethasone-induced apoptosis

Abstract: Because of the increasing use of IFN-␣ in both induction and maintenance therapy for multiple myeloma (MM), its effect on growth and apoptosis of myeloma cells is important to consider. To investigate the role of IFN-␣ on the growth of myeloma cells, we have studied its effects on the response of interleukin 6 (IL-6)-dependent myeloma cell line (ANBL6) and IL-6-independent myeloma cell line (C2E3) in the presence of IL-6 and dexamethasone (Dex). We found that although IFN-␣ is a potent inhibitor of proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
(39 reference statements)
2
13
0
Order By: Relevance
“…(34)(35)(36)(37) In a previous work we described that rat placental culture supernatants induced asymmetric IgG glycosylation of anti-DNP IgG1 monoclonal antibodies synthesized by hybridoma cells, which was correlated with a placental supernatant cytotoxic effect on the cells. (24) In addition we have recently reported that heat shock induction in these cells correlated with asymmetric IgG antibody synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(34)(35)(36)(37) In a previous work we described that rat placental culture supernatants induced asymmetric IgG glycosylation of anti-DNP IgG1 monoclonal antibodies synthesized by hybridoma cells, which was correlated with a placental supernatant cytotoxic effect on the cells. (24) In addition we have recently reported that heat shock induction in these cells correlated with asymmetric IgG antibody synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the action of dexamethasone on apoptosis, cell proliferation, as well as on antibody synthesis by myeloma cell lines can be reverted by adding IL-6 to the cells. (35,37,40) To assess such hypothesis, we first evaluated the 112D5 ability to synthesize IL-6, and after that, whether it could be modulated by the corticoid. Interleukin-6 was detected in supernatants of hybridoma cell lysates, but no effect of dexamethasone was observed on IL-6 concentration assessed in the cell lysates by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of apoptosis was found to be concurrent with the induction of both AP-1 and STAT binding activity. 30 In any case, the results obtained by in vivo studies appear to be more homogeneous in reference to the effectiveness of IFN in the treatment of patients with multiple myeloma. Clinical trials performed to evaluate the efficacy of IFN in the treatment of human multiple myeloma have demonstrated that the treatment of previously untreated patients with IFN is not useful because the response rate is lower than that obtained with chemotherapy.…”
Section: Immunotherapy Of Multiple Myelomamentioning
confidence: 94%
“…However, an antagonizing effect for IFNs on TRAILinduced caspase-8 activation has been identified (10). In several studies, IFN-α protected myeloma cells from dexamethasoneinduced apoptosis (7,14), suggesting antiapoptotic activity for IFNs in myeloma. However, molecular mechanisms for antiapoptotic effects of IFNs in malignancies have remained unclear.…”
Section: Introductionmentioning
confidence: 99%